Votata a llengua nosta: Baroque Naples and The Language Question - Canepa, Nancy L. (Quaderni d'Italianistica, 2021)
One of the most striking reactions to the Renaissance codification of literary Italian was the development of dialects as “alternative” literary languages with their own distinct canons. During the seventeenth century, Naples, the undisputed centre of this experimentation, produced a remarkable corpus of original masterpieces by Giambattista Basile, Giulio Cesare Cortese, and others; translations into Neapolitan of Italian and Latin classics, old and new; and linguistic treatises and paratextual materials in praise of Neapolitan. What did this activity mean? How and why did these authors assert their alterity by constructing an ideal poetic community through their Neapolitan works? How did the questioning of the idea of a monolithic literary language relate to a wider interrogation of the traditional system of genres and of the concept itself of literary property? This essay explores these questions by onsidering the role of the supporting materials of paratexts and translations in the construction and legitimization of the Neapolitan corpus.